Summary of Self-Management Program for Patients with CKD: A Systematic Review - Hendrik Prayitno Luawo; Yulia Indah Permata; Ulfa Nur Rohmah; Waluyo Waluyo; Saskiyanti Ari Andini (Universitas Airlangga, 2019)
Background: Self-management is an important step in preventing and impeding the progression of chronic kidney disease. The effective support and encouragement of self-management in patients with chronic kidney disease is therefore required. The aim of this study was to examine the effectiveness of a self-management program improving the quality of life on patients with CKD.Method: The literature review used the keywords ‘chronic kidney disease’, ‘self-management program’ and ‘quality of life’. From the article search using “AND” as well, only 8 studies met the inclusion criteria. Across the 8 studies, 592 participants and a mean 147 per trial were included within the middle age group.Discussion: The types intervention were a heterogenous. CKD self-management program, renal education and exercise intervention, the EASE program, the KDE program, and a CKD Educational Program recommended to improve quality of life.Consclusion: The education and exercise intervention had a positive effect on the physical and mental health and well-being of the patients with CKD. Therefore early education about renal disease improves quality of life and treatment outcomes in patients with CKD who are on dialysis.